Plasma VEGF-related polymorphisms are implied in autoimmune thyroid diseases. (18th May 2016) - Zaaber, Ines; Rancier, Marc; Stathopoulou, Maria G.; Saleh, Abdelsalam; Marmouch, Héla; Masson, Christine; Murray, Helena; Kurth, Mary Jo; Lamont, John; Fitzgerald, Peter; Mahjoub, Selvia; Said, Khaled; et al.
Abstract: Autoimmune thyroid diseases (AITD), including Graves' disease (GD) and Hashimoto thyroiditis (HT), are complex multifactorial diseases. Vascular endothelial growth factor (VEGF) is implicated in various inflammatory diseases, especially autoimmune diseases. Our aim was to elucidate the relationships between plasma VEGF levels and four genome-wide association study-identified single nucleotide polymorphisms (SNPs) related to VEGF with AITD in Tunisian patients. A total of 364 healthy controls and 389 patients with AITD were genotyped for the SNPs rs6921438, rs4416670, rs6993770 and rs10738760. Levels of thyroid hormones and antibodies were quantified simultaneously with plasma VEGF after a period of six months of treatment. We found that the minor alleles of rs10738760 and rs6921438 are associated with the presence of GD. A allele of rs10738760 polymorphism is associated with increased plasma levels of free tri-iodothyronin (FT3) while no relationship was found with circulating VEGF plasma levels after six months of treatment. We also showed that the T allele of rs4416670 polymorphism was associated with increased risk of hyperthyroidism in patients treated for six months, independently of their initial diagnosis. There was no significant association between the SNPs and the risk for HT compared with controls. This study shows that AITD are influenced by 3 SNPs linked to VEGF circulating levels. Whereas rs10738760 appeared specific to GD and FT3 production after six months of treatment, rs6921438 and rs4416670 were implicated in the risk for GD. This study opens new ways to test pharmacogenomics concepts in the future especially in GD in which recurrence prognosis is still challenging.